2020
DOI: 10.32718/nvlvet9821
|View full text |Cite
|
Sign up to set email alerts
|

Histogical structure of the thyroid gland in rabbits with different types of autonomous tonus

Abstract: The research was aimed at investigating the influence of the aggregated tonus of sympathetic and parasympathetic centers on the rabbit’s thyroid gland morphology. For this purpose, the rabbit males (Oryctolagus cuniculus (Linnaeus, 1758)) of Blanc de Termond breed at the age of four months, passed an electrocardiographic and variation pulsometry study. According to the results, the animals were divided into three groups: rabbits with sympathicotonia (18 animals), rabbits with normotonia (5 animals) and rabbits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
1
1
Order By: Relevance
“…On the other hand, the results of this study regarding the capsule for both animals did not agree with the findings of the study of the thyroid gland in the African giant rat [27] and white hybrid pigs [25], where it was found that the capsule is consist of a single layer of connective tissue. Furthermore, it did not agree with the study on black Bengal goat thyroid gland [28] and rabbits [29], as the capsule was found to be composed of three layers: inner layers and outer layer consisting of connective tissue and middle layer consisting of fatty and nervous tissue. The reason for the difference in the results of this study with the previous studies mentioned above may be due to the need for energy to accomplish the function and to the different nature of the environment as well as the variation in the sizes of animals.…”
Section: Discussioncontrasting
confidence: 63%
“…On the other hand, the results of this study regarding the capsule for both animals did not agree with the findings of the study of the thyroid gland in the African giant rat [27] and white hybrid pigs [25], where it was found that the capsule is consist of a single layer of connective tissue. Furthermore, it did not agree with the study on black Bengal goat thyroid gland [28] and rabbits [29], as the capsule was found to be composed of three layers: inner layers and outer layer consisting of connective tissue and middle layer consisting of fatty and nervous tissue. The reason for the difference in the results of this study with the previous studies mentioned above may be due to the need for energy to accomplish the function and to the different nature of the environment as well as the variation in the sizes of animals.…”
Section: Discussioncontrasting
confidence: 63%
“…Several previous studies indicate that there are some differences in the capsule structure that surrounds the thyroid gland, as the study of the thyroid gland goat [18], the local Iraqi sheep [16], and the African giant mouse [19] indicates that the capsule consists of a thin layer of connective tissue. While the studies of the thyroid gland in Indian buffalo [20], the black Bengal goat [21] and rabbit [22] observed that the thyroid gland consists of three layers: outer, middle, and inner layers, whereas this study showed that the capsule consists of two layers, an outer and inner layer, and a layer of fatty tissue interferes with the outer layer. This is consistent with the findings of the guinea pig [14], Hussin and Al-Taay's [23] study on Iraqi buffalo, domestic rabbits [24], and other studies.…”
Section: Discussionmentioning
confidence: 63%